Sistem Informasi Akademik Berbasis Website Pada SMA Negeri 18 Luwu Utara - S Sisilia; A Apriyanto; Muhlis Muhallim (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2022)
The purpose of this research to design and build academic information system at SMA Negeri 18 Luwu Utara. The research method used is qualitative method with data colllection techniques using observation and documentation method. The aplication of academic of academic information system developed by using waterfall system development method. As the software used in the desain and implementation system using visual studio code as the system desain. Application of academic information system includes master data, user data, academic data, and report value. The application was built has been tested to user so that an application that run very well is obtained